Using spreadsheet to teach limit among college students - Kok Fui, C.; Syed Zamri, S.N.A. (2013)
The commandment of e-N definition is essential in order to learn the concept of limit. In Malaysia, students will only learn this definition in the tertiary level due to its complicated structure. Although technology component was introduced in secondary schools in year 2006, e-N definition was still not part of the syllabus as if learning of this definition was still impossible to secondary students. Furthermore, because of incorrect notions of limit perceived at the secondary level, students find learning e-N definition to be difficult in the tertiary level. These have motivated the researcher to create a technology-aided module that is able to remediate these difficulties. The potential of spreadsheet in enhancing understanding about limit is addressed in this study. A spreadsheet module about limit learning was designed, and its effectiveness was tested in a pre-test-and-post-test quasi experiment as compared to the traditional paper-and-pencil method. Through data analysis, it was found that participants in the study gained a significant improvement in understanding the concept, implying that spreadsheet-aided environment made learning e-N definition possible even in the secondary level.